Anticoagulation Therapy Reduces Recurrent Stroke in Embolic Stroke of Undetermined Source Patients With Elevated Coagulation Markers or Severe Left Atrial Enlargement - Patel, Kishan (Front Neurol, 2021)
Background: The objective of this study was to evaluate if anticoagulation therapy reduces recurrent stroke in embolic stroke of undetermined source (ESUS) patients with left atrial enlargement (LAE) or abnormal markers of coagulation and hemostatic activity (MOCHA) compared to antiplatelet therapy. Methods: ESUS patients from January 1, 2017, to June 30, 2019, underwent outpatient cardiac monitoring and the MOCHA profile (serum d-dimer, prothrombin fragment 1.2, thrombin–antithrombin complex, and fibrin monomer). Anticoagulation was offered to patients with abnormal MOCHA (≥2 elevated markers) or left atrial volume index 40 mL/m(2). Patients were evaluated for recurrent stroke or major hemorrhage at routine clinical follow-up. We compared this patient cohort (cohort 2) to a historical cohort (cohort 1) who underwent the same protocol but remained on antiplatelet therapy. Results: Baseline characteristics in cohort 2 (n = 196; mean age = 63 ± 16 years, 59% female, 49% non-White) were similar to cohort 1 (n = 42) except that cohort 2 had less diabetes (43 vs. 24%, p = 0.01) and more tobacco use (26 vs. 43%, p = 0.04). Overall, 45 patients (23%) in cohort 2 initiated anticoagulation based on abnormal MOCHA or LAE. During mean follow-up of 13 ± 10 months, cohort 2 had significantly lower recurrent stroke rates than cohort 1 (14 vs. 3%, p = 0.009) with no major hemorrhages. Conclusions: Anticoagulation therapy in a subgroup of ESUS patients with abnormal MOCHA or severe LAE may be associated with a reduced rate of recurrent stroke compared to antiplatelet therapy. A prospective, randomized study is warranted to validate these results.